1992
DOI: 10.1128/mcb.12.8.3499
|View full text |Cite
|
Sign up to set email alerts
|

The gene for a novel human lamin maps at a highly transcribed locus of chromosome 19 which replicates at the onset of S-phase.

Abstract: A previously described human DNA fragment which is replicated early in S-phase of HL-60 cell DNA (C. (7,19). Elucidation of the underlying mechanisms will constitute a major step in understanding the nuclear dynamics of the process, cell growth, and differentiation.We have previously described the isolation and cloning of a human DNA fragment (pB48; 1,560 bp) that belongs to the fraction of DNA replicated at the onset of S-phase in synchronized HL-60 cells (35). Analysis of this fragment indicated that it der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
111
0
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(115 citation statements)
references
References 33 publications
2
111
0
2
Order By: Relevance
“…This region was shown to contain a strong promoter for the downstream transcription unit; a key feature ofthis promoter is the presence of a basic helix-loop-helix protein binding motif that was shown to bind in vitro to the USF/MLTF protein (23); interestingly, such motif also fits the binding consensus for the Myc/Max complex (24), whose function in regulating cell proliferation is suggested by several studies (25) [incidentally, the c-myc gene domain is amplified in HL-60 cells (26)]. An evolutionary conserved (A+T)-rich region (22) can be envisaged in the proximity of the origin, as is the case for well-defined replication origins of different organisms (27)(28)(29).…”
Section: ~-F )W Lmentioning
confidence: 99%
See 2 more Smart Citations
“…This region was shown to contain a strong promoter for the downstream transcription unit; a key feature ofthis promoter is the presence of a basic helix-loop-helix protein binding motif that was shown to bind in vitro to the USF/MLTF protein (23); interestingly, such motif also fits the binding consensus for the Myc/Max complex (24), whose function in regulating cell proliferation is suggested by several studies (25) [incidentally, the c-myc gene domain is amplified in HL-60 cells (26)]. An evolutionary conserved (A+T)-rich region (22) can be envisaged in the proximity of the origin, as is the case for well-defined replication origins of different organisms (27)(28)(29).…”
Section: ~-F )W Lmentioning
confidence: 99%
“…In the previous years, we demonstrated that a 1560-bp DNA fragment [B48, selected from a mini-library of HL-60 cell DNA containing fragments derived from the replicons activated at the beginning of the S phase (16)] was in fact replicated in the very first minute of the S phase in HL-60 synchronized cells (22) and, thus, presumably very close to, or even coincident with, an origin. We sequenced 13.7 kb around the initial isolate, and we observed that this genomic region, mapping on band p13.3 of chromosome 19, contains the final portion of the lamin B2 gene and, downstream of it, another gene (ppvl), transcribed in the same direction and coding for a still unidentified product [ Fig.…”
Section: ~-F )W Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is suggested that lamins play a key role in providing structural support to the nuclear membrane. Next to the ubiquitously expressed B-type lamins, lamins B1 and B2 [3,4], most highly differentiated cells express A-type lamins. These proteins, lamin A, lamin AD10, and lamin C, are encoded by the A-type lamin (LMNA) gene [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Human LMNB1 encodes lamin B1 and LMNB2 encodes lamin B2. These "B-type" lamins are expressed in all or most somatic cells [19,20]. All of these proteins, except lamin C, are posttranslationally modified by farnesylation and carboxymethylation at a carboxyl-terminal cysteine-aliphatic-aliphatic-any ("CAAX") amino acid motif.…”
Section: Nuclear Envelopementioning
confidence: 99%